Stakeholder Power and Sustainability Disclosure: Stakeholder Salience Perspective - Majdi, Suria; Mohd Saleh, Norman; Abdullah, Maizatulakma; Alias, Norazlan (The South East Asian Journal of Management, 2023)
Research Aims: This study tests the effects of different stakeholder power (shareholders, employees, customers, business partners, community, government, NGOs, and media) on sustainability disclosure using stakeholder salience theory. Extending from this perspective, this study makes separate assumptions for each stakeholder and determines which one had the most power over sustainability disclosure. Design/Methodology/Approach: The study adopts a journalism (i.e., news framing) approach and observes the element of power in sustainability disclosure using content analysis. The sample comprises of panel data of 140 listed firms in the construction and property sector in Malaysia. Research Findings: The results show that the employees, community and media power are positively related to sustainability disclosure. This study improves our understanding of the factors determining firms' disclosure by demonstrating that market stakeholders (shareholders, employees, customers and business partners) are not perceived as necessary by managers concerning sustainability disclosure. Theoretical Contribution/Originality: Common studies view all stakeholders to be taken homogenously into consideration in business decision making. Few studies focus on the power of stakeholders in influencing disclosure is lacking. Managerial Implication in the South East Asian Context: This study gives insight on which stakeholder is the most important in rank and the finding informs managers to draft a stakeholder management plan and budget, given that such activities can increase firm value. Research Limitation & Implications: This research however did not investigate the dynamics of stakeholder power along with the existence of other salience factors, i.e., the legitimacy and urgency factors.